Digital currency of the Central bank in Russia and in the world: current status and development prospects - D. V. Baranov; P. S. Shcherbachenko (Вестник университета, 2024)
The article presents an analysis of the main trends and prospects for the development of central bank digital currencies (hereinafter referred to as CBDC) in the global context and in the Russian Federation (hereinafter referred to as RF, Russia), comparing them with cryptocurrencies and traditional fiat currencies. Special attention is given to identifying such advantages of digital currencies over conventional ones as independence, security, transparency and the possibility of using smart contracts. However, CBDC, unlike cryptocurrencies, are subject to control and depend on the actions of central banks. The article includes an overview of the experience of various countries such as Russia, China, India, United Arab Emirates, France, and Nigeria. The analysis of the ratio of commission and interest income in the activities of Russian banks has also been conducted. It has been found that commission income in the banking sector is important, and the impact of introducing the digital ruble by the Central Bank of Russia on the banking system has been assessed. In conclusion, recommendations are proposed for introduction of the digital ruble into the daily activities of Russian banks, including consideration of the difficulties for them and active customer engagement as well as the need to create a separate organisation to control the operations of the digital ruble.